2015
DOI: 10.1055/s-0035-1556568
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Chronic Low-Grade Inflammation in the Pathophysiology of Polycystic Ovary Syndrome

Abstract: Polycystic ovary syndrome (PCOS) has become increasingly common over recent years and is associated with reproductive features as well as cardiometabolic risk factors, including visceral obesity, dyslipidemia and impaired glucose homeostasis, and potentially cardiovascular disease. Emerging evidence suggests that these long-term metabolic effects are linked to a low-grade chronic inflammatory state with the triad of hyperinsulinemia, hyperandrogenism, and low-grade inflammation acting together in a vicious cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 119 publications
(208 reference statements)
2
68
0
Order By: Relevance
“…Women with PCOS present with a range of features including reproductive, metabolic and psychological features . While insulin resistance (IR) and hyperandrogenism are the key hormonal disturbances underpinning the pathophysiology of PCOS, the long‐term metabolic effects of PCOS may be partly attributed to additional effects of sympathetic dysfunction and chronic low‐grade inflammation …”
Section: Introductionmentioning
confidence: 99%
“…Women with PCOS present with a range of features including reproductive, metabolic and psychological features . While insulin resistance (IR) and hyperandrogenism are the key hormonal disturbances underpinning the pathophysiology of PCOS, the long‐term metabolic effects of PCOS may be partly attributed to additional effects of sympathetic dysfunction and chronic low‐grade inflammation …”
Section: Introductionmentioning
confidence: 99%
“…Studies have been shown that PCOS is a chronic low-level inflammation and this chronic disease can be a potential cause of the long-term consequence of PCOS (3,4). In vitro studies suggest that pro-inflammatory stimuli are capable of up-regulation of the steroidogenic enzymes for the production of androgens in theca cells of the ovary (hyperandrogenism) (5). ''This concept raises the possibility that inflammation may be capable of directly inducing hyperandrogenism in PCOS'' (6).…”
Section: Introductionmentioning
confidence: 99%
“…PCOS is associated with insulin resistance and lowgrade chronic inflammation, each of which increases the risk of the other, resulting in a vicious cycle in the pathophysiology of PCOS [40,41]. Dysregulation of the sympathetic nervous system is also involved in the etiology of PCOS [41].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of the sympathetic nervous system is also involved in the etiology of PCOS [41]. Previous studies have demonstrated that some genetic variants of genes such as metalloproteases meprin-α (MEP1A) and estrogen receptor 1 (ESR1) are associated with glucose and insulin metabolism and inflammation in PCOS women [42,43].…”
Section: Discussionmentioning
confidence: 99%